Implementasi Perdagangan Ekspor Pisang Cavendish PT. Great Giant Pineapple (GGP) dengan Jepang pada Tahun 2022 - Kurnia Santi; Tanti Nurgiyanti; Bagus Subekti Nuswantoro; Yeyen Subandi (Yayasan Literasi Sains Indonesia, 2023)
This study aims to determine the implementation of the cavendish banana export trade at PT. Great Giant Pineapple (Indonesia) with Japan. The theory used in this study is the theory of comparative advantage according to David Ricardo, using qualitative research methods. The results showed that the implementation of the cavendish banana export trade by PT. Great Giant Pineapple (Indonesia) with Japan was realized through several stages, namely the purchasing stage which consisted of a purchasing order (PO), namely a document made to show the goods purchased, signing the SO and goods entering the warehouse. In addition, the sales stage which consists of sales orders (SO), travel documents, sales invoices, and receipt of accounts receivable, and finally, the export process stage which consists of stuffing goods, sending goods to the port to the destination country, namely Japan, then distributing it to buyers. . The documents needed in implementing PT GGP's export trade to Japan include the main documents, namely invoices, packing lists, shipping instructions, PEB and bills of lading, as well as supporting documents consisting of COO, health cert, and phytosanitary cert.